The Relationship Between Adherence to The Consumption of Blood Supplement Tablets with the Incidence of Anemia in Pregnant Women in The Working Area of The Krebet Health Center, Madiun District - Rohmatin, Hannisa Nur; Mustikanigrum, Fitriana (International Journal of Science and Society, 2024)
Anemia is a common health problem in pregnant women. One of the causes of anemia is inadequate iron absorption. According to RISKESDAS statistics, 78% of pregnant women suffer from anemia in 2021. According to statistical data from the Krebet Health Center, the incidence of anemia in pregnant women will reach 7.75% in 2022. This research examines how compliance with consuming blood supplement tablets affects the incidence of anemia in pregnant women. Research Method: This research uses a cross-sectional design. The sampling technique used consecutive sampling involving 51 respondents. The data collection technique for the amount of compliance uses the MMAS-8 questionnaire and for the incidence of anemia uses secondary data. Test the data hypothesis using the Chi-square test. Research Results: The research results from 51 respondents, 49.01% were compliant, 50.9% were non-compliant. 60.7% of respondents experienced anemia (31 respondents), 39.3% of respondents were not anemic (20 respondents). A p value of 0.000 (< 0.05) means that there is a relationship between the incidence of anemia and compliance Conclusion: There is a relationship between compliance with the consumption of blood supplement tablets and the incidence of anemia in pregnant women in the working area of the Krebet Community Health Center, Madiun Regency.